Interlaboratory Comparison of Branched GDGT Temperature and pH Proxies Using Soils and Lipid Extracts - Cindy De Jonge; Francien Peterse; Klaas G. J. Nierop; Thomas M. Blattmann; Marcelo Alexandre; Salome Ansanay‐Alex; Thomas Austin; Mathieu Babin; Edouard Bard; Thorsten Bauersachs; Jerome Blewett; Brenna Boehman; et al. (Geochemistry, Geophysics, Geosystems)
Abstract Ratios of glycerol dialkyl glycerol tetraethers (GDGT), which are membrane lipids of bacteria and archaea, are at the base of several paleoenvironmental proxies. They are frequently applied to soils as well as lake‐ and marine sediments to generate records of past temperature and soil pH. To derive meaningful environmental information from these reconstructions, high analytical reproducibility is required. Based on submitted results by 39 laboratories from across the world, which employ a diverse range of analytical and quantification methods, we explored the reproducibility of brGDGT‐based proxies (MBT′5ME, IR, and #ringstetra) measured on four soil samples and four soil lipid extracts. Correct identification and integration of 5‐ and 6‐methyl brGDGTs is a prerequisite for the robust calculation of proxy values, but this can be challenging as indicated by the large inter‐interlaboratory variation. The exclusion of statistical outliers improves the reproducibility, where the remaining uncertainty translates into a temperature offset from median proxy values of 0.3–0.9°C and a pH offset of 0.05–0.3. There is no apparent systematic impact of the extraction method and sample preparation steps on the brGDGT ratios. Although reported GDGT concentrations are generally consistent within laboratories, they vary greatly between laboratories. This large variability in brGDGT quantification may relate to variations in ionization efficiency or specific mass spectrometer settings possibly impacting the response of brGDGTs masses relative to that of the internal standard used. While ratio values of GDGT are generally comparable, quantities can currently not be compared between laboratories.